2021
DOI: 10.1002/jmv.27356
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota dysbiosis associated with plasma levels of Interferon‐γ and viral load in patients with acute hepatitis E infection

Abstract: Few studies have focused on the effect of hepatitis E virus (HEV) infection on gut microbiota. To explore the relationship between changes in gut microbiota and inflammatory factors and viral load, we conducted a comparative study of 33 patients with acute hepatitis E (AHE) patients and 25 healthy controls (HCs) using highthroughput 16S ribosomal ribonucleic acid gene sequencing. Shannon and Simpson's indices showed no significant differences in bacterial diversity between the AHE and HCs groups. Proteobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
(43 reference statements)
2
17
0
Order By: Relevance
“…Like HAV, only a few reports have been published on the alteration of the intestinal microbiota in acute HEV infection. The composition of the microbiota is altered in patients with acute hepatitis E (AHE), compared with that in healthy subjects, and the abundance of some bacteria (Proteobacteria, Gammaproteobacteria, and Enterobacteriaceae) is related to the amount of interferon-gamma secreted [ 95 ]. In this report, the presence of Gammaproteobacteria was positively correlated with the serum alanine transaminase and total bilirubin levels, suggesting that the presence of Gammaproteobacteria may serve as an indicator to identify patients with AHE and to more accurately predict the severity.…”
Section: Hepatitis Virusmentioning
confidence: 99%
“…Like HAV, only a few reports have been published on the alteration of the intestinal microbiota in acute HEV infection. The composition of the microbiota is altered in patients with acute hepatitis E (AHE), compared with that in healthy subjects, and the abundance of some bacteria (Proteobacteria, Gammaproteobacteria, and Enterobacteriaceae) is related to the amount of interferon-gamma secreted [ 95 ]. In this report, the presence of Gammaproteobacteria was positively correlated with the serum alanine transaminase and total bilirubin levels, suggesting that the presence of Gammaproteobacteria may serve as an indicator to identify patients with AHE and to more accurately predict the severity.…”
Section: Hepatitis Virusmentioning
confidence: 99%
“…Here, timing of our sampling is highly relevant to the interpretation of our results. Alterations in an individual’s microbiome may occur in the context of acute disease, 65 whether from infection, dietary changes, medication, usage, and/or immune function; however, an individual’s microbiome regresses over time 66 to reflect a stable baseline microbiome 67,68 . Thus, faecal microbiome samples collected 9 months after the start of illness may represent baseline individual microbiome, which, in our study, did not relate to symptom duration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, transcriptomics provides complete genomic data on the evolutionary relationships of avian HEV, which helps us further understand the evolution of HEV. Besides, Wu et al (2022a) performed the 16S ribosomal ribonucleic acid gene sequencing, and they found that gut microbiota dysbiosis is associated with plasma levels of Interferon-γ and viral load in patients with acute hepatitis E infection. Overall, the investigation on HEV infection and related diseases using multi-omics are less, which requires more efforts.…”
Section: Multi-omics In Hepatitis E and Related Diseasesmentioning
confidence: 99%